(untitled) - Glickman, Carl D. (San Francisco, Calif., 2003)
Glickman (education, Southwest Texas State University) draws on his experience as director of a school improvement program dealing with some 100 diverse K-12 schools. He offers advice on leadership formats that support truly democratic education, and provides examples of curriculum and methods for improving achievement and building citizenship capabilities.
Keywords: Educational leadership,School improvement programs,Education; Aims and objectives; United States,United States,United States